Results of prosthetics in patients with changing volumes of their hip stumps - Vatolinskiy, Leonid; Shchetinina, Lyubov; Baev, Pavel; Korneev, Sergey; Kabanenko, Iryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
The designed hip prostheses with split sleeves, which make it possible to regulate their volume parameters, enable doctors to perform rehabilitation of geriatric patients, disabled people during their primary prosthetics as well as a complex bulk of patients with vascular pathology on a higher level, to increase mobility of injured people and their independence in regulating the size of their sleeve, and to provide the patients with a more comfortable use of prostheses.